2015
DOI: 10.1016/j.funbio.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

H2O2 plays an important role in the lifestyle of Colletotrichum gloeosporioides during interaction with cowpea [Vigna unguiculata (L.) Walp.]

Abstract: Plant-fungus interactions usually generate H(2)O(2) in the infected plant tissue. H(2)O(2) has a direct antimicrobial effect and is involved in the cross-linking of cell walls, signaling, induction of gene expression, hypersensitive cell death and induced systemic acquired resistance. This has raised the hypothesis that H(2)O(2) manipulation by pharmacological compounds could alter the lifestyle of Colletotrichum gloeosporioides during interaction with the BR-3-Tracuateua cowpea genotype. The primary leaves of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 51 publications
1
11
0
4
Order By: Relevance
“…Impala) were infiltrated with 0.5 μM DPI (Sigma-Aldrich, St. Louis, MO, USA) in 0.05% DMSO using a disposable, plastic needleless syringe. The leaves that were infiltrated with 0.05% DMSO served as controls (Eloy et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Impala) were infiltrated with 0.5 μM DPI (Sigma-Aldrich, St. Louis, MO, USA) in 0.05% DMSO using a disposable, plastic needleless syringe. The leaves that were infiltrated with 0.05% DMSO served as controls (Eloy et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…The role of ROS in the infection process of hemibiotrophic pathogens, such as P. infestans remains controversial (Shetty et al 2007;Henriquez et al 2012;Thomazella et al 2012;Eloy et al 2015). The present study focused on potato biochemical defense responses induced during the early biotrophic and the late necrotrophic stages of P. infestans on resistant and susceptible cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…During the plant-pathogen interaction, the generated ROS may play a dual role; its production in cells is highly effective against biotrophic pathogens, whereas high accumulation of H 2 O 2 has been reported to help the colonization process of plant tissues by necrotrophic pathogens (Noorbakhsh and Taheri 2016). For the hemibiotrophic pathogens, the role of H 2 O 2 in the infectious process is still poorly understood (Shetty et al 2007;Henriquez et al 2012;Thomazella et al 2012;Eloy et al 2015). In-depth studies are necessary to fully elucidate the balance between the antioxidant system and the concentration of ROS during the infection process of P. infestans.…”
Section: Introductionmentioning
confidence: 99%
“…Similar type of infection was also observed in guava (Moraes et al, 2013). However, in cowpea leaves, it was reported that C. gloeosporioides attempt to gain entry into leaf tissues through stomatal openings (Eloy et al , 2015). Under in vitro culture conditions on PDA medium, C. gloeosporioides typically exhibited growth stages like germination of conidia after 3 hpi and appressoria formation after 36 hpi; but never displayed the development of primary and secondary hyphae under these conditions.…”
Section: Discussionmentioning
confidence: 99%